Comparative assessment of the clinical efficacy of various amlodipine isomers in 1st and 2nd degree arterial hypertension patients - Ermakov, Dmitriy; Pashanova, Olga (Bangladesh Journal of Medical Science, 2021)
Objective: The paper presents the results of clinical trials of medications based on S-amlodipine and S/R-amlodipine. Materials and methods: A total of 140 patients diagnosed with arterial hypertension of I and II degree were included into study, in particular, 70 patients with 1st degree and another 70 patients with 2nd degree hypertensive disease. A group consisted of 80 male (57%) and 60 female patients (43%) aged from 45 to 73 years. The average age of the examined patients was 62.1±5.8 years. Duration of the disease was established between 1 and 22 years (12.5±1.2 years on average). Results and discussion: The stereoselectivity mechanisms of the studied amlodipine enantiomers were found to initiate the activity of only one S-amlodipine isomer. Applying S-amlodipine in treatment was proved to improve significantly the clinical results, facilitate the course of hypertensive disease, and normalize the structure and functional heart condition. After 8 weeks of amlodipine-based treatment, the diastolic pressure in groups receiving S-amlodipine reduced by 20-25% and systolic pressure reduction was between 20% and 31%. Among patients taking the original amlodipine medication consisting of S and R enantiomers, the diastolic pressure decrease was between 19.4% and 24%, and the systolic pressure reduced from 16.7% to 27.37%. Conclusions: By using S-amlodipine, the prescribed medication dosage can be reduced by 50%, which allows diminishing the drug load on the body and lessen the side effects. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.439-448